2021
DOI: 10.1021/acsami.1c14531
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Assisted Development of Sensitive Electrode Materials for Mixed Potential-Type NO2Gas Sensors

Abstract: Yttrium-stabilized zirconia (YSZ)-based mixed potential-type NO x sensors have broad application prospects in automotive exhaust gas detection. Great efforts continue to be made in developing high-performance sensitive electrode materials for mixed potential-type NO2 gas sensors. However, only five kinds of new sensing electrode materials have been developed for this type of gas sensor in the last 3 years. In this work, four different tree-based machine learning models were trained to find potentially sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Compared with other gas detection techniques, chemiresistive sensors are superior in terms of low cost, easy fabrication, not needing a professional operator, and real-time online monitoring. 1–11 However, the predominant sensing materials, metal oxides, are still limited by high working temperature, low sensitivity at room temperature and selectivity. 1 Researchers have found that the free charges generated by light irradiation can effectively enhance the sensitivity of metal oxides at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other gas detection techniques, chemiresistive sensors are superior in terms of low cost, easy fabrication, not needing a professional operator, and real-time online monitoring. 1–11 However, the predominant sensing materials, metal oxides, are still limited by high working temperature, low sensitivity at room temperature and selectivity. 1 Researchers have found that the free charges generated by light irradiation can effectively enhance the sensitivity of metal oxides at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical resistance sensor relying on the charge transfer between the target gas and the functional material is widely used. [8][9][10][11][12][13] As the Internet of Things (IoT) continues to develop, the demand for sensors with enhanced portability, high sensitivity, and low operating temperature is increasing. [14][15][16][17][18][19] This has led to a significant requirement for developing novel materials to fabricate room-temperature NO 2 gas sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, with the help of machine learning, Wang et al screened out 13 new sensitive electrode materials for NO 2 gas sensors in a short period of time in a targeted and efficient manner. 25 Nevertheless, there is no report on how to identify ethanol from moisture because perovskites are responsive to both. As is known, there is a lot of moisture in the breath of people who are drunk, where ethanol accounts for a small proportion compared to water vapor.…”
Section: Introductionmentioning
confidence: 99%